Pejalan Kaki atau Pedagang Kaki Lima: Dilema Keberpihakan - Ma'arif, Syamsul; Rahmawati, Ratih (Wacana Publik, 2024)
Street vendors are part of the economic activities that are the activities of the informal sector. The rapid growth of street vendor activity without good management can lead to deviations in urban planning. The location along the road corridor is a strategic location with easy access to open to the public, as happened in the Yellow Bamboo Market Bandar Lampung, sidewalks are used by street vendors to trade, so pedestrian access is almost completely lost. The purpose of this study is to identify the use of sidewalks and roadsides by PKL and factors that influence and the impact of pedestrian access closure due to the use of sidewalks for commercial activities by PKL in Bandar Lampung City. So that the impacts caused are twofold, namely Positive and Negative Impacts. Based on the results of the study, it can be said that the implementation of pkl procurement in the Yellow Bamboo Market in Bandar Lampung City has not been effective in overcoming PKL problems. This is because the PKL was not obeyed and order was not achieved as expected by the Bandar Lampung City Government